PEOPLE’S KNOWLEDGE ABOUT THE IMPORTANCE OF ENVIRONMENTAL EDUCATION - Aparecida Paes, Aline; Velozo da Silva, Gleycon; de Oliveira Ramos, Tatiana (Journal of Interdisciplinary Debates, 2023)
Environmental Education is essential in people’s lives. Not all students have had the opportunity to participate in Environmental Education projects during their normal study time, however, today many students are involved in projects that help them build social values and protect the planet. The objective of this research was, through an electronic questionnaire, to verify the degree of knowledge that people have about Environmental Education. In total, 1,024 people from all Brazilian states responded to the questionnaire, with the highest percentage of responses from the female audience, aged between 15 and 45 years, who studied in public schools. Most participants have satisfactory knowledge about what Environmental Education is, however a high number of people stated that they have never participated in an Environmental Education project.